CORPORATE GOVERNANCE COMMITTEE AND FINANCIAL PERFORMANCE OF HEALTHCARE FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
The study examined the effect of corporate governance committee on financial performance of healthcare firms in Nigeria. The specific objective was to determine the extent to which audit committee, risk committee, nomination committee and remuneration committee affect return on assets of listed healthcare firms in Nigeria. The study adopted the ex-post facto research design. The population comprised eight (8) healthcare firms listed on Nigerian Exchange Group. The study used purposive sample to select six healthcare firms. Secondary data for the study were obtained from the annual reports of the sampled firms, over an eleven year period (2012 to 2022). The descriptive statistics and ordinary least square regression technique were used to analyze the data. The result of the hypotheses tested revealed the following: Audit committee has a non-significant but positive effect on return on assets of listed healthcare firms in Nigeria; risk management committee has a significant but negative effect on return on assets of listed healthcare firms in Nigeria; nomination committee has a positive but non-significant effect on return on asset of listed healthcare firms in Nigeria; remuneration committee has a significant but negative effect on return on assets of listed healthcare firms in Nigeria. In conclusion, optimizing the composition and functioning of governance committees will enable healthcare firms to better align with organizational goals and enhance financial performance. The study therefore recommends that firm should sustain frequencies of audit committee meetings, so as to ensure that the committee has enough time to take decisions that are efficient and effective in enhancing better firm performance
Keywords: Audit Committee; Corporate Governance Committee; Financial Performance; Nomination Committee; Remuneration Committee; Return on Assets; Risk Committee